BLOCKCHAIN TECHNOLOGY FOR LAND REGISTRATION IN NIGERIA: A REVIEW OF OPPORTUNITIES AND CHALLENGES - Okoli, Franklin U.; Oludiji, S. M.; Ofoegbunam, E. I.; Oyesiji, A. O.; Akindiya, O. M. (FUDMA JOURNAL OF SCIENCES, 2024)
Land registration is critical for ensuring legal certainty and economic stability, yet Nigeria's system is plagued by inefficiencies, corruption, and inadequate technical infrastructure. These challenges result in prolonged processing times, high registration costs, insufficient technical skills, unqualified staff, excessive land charges, and an unclear legal framework. Additionally, institutional inefficiencies, ignorance among landowners regarding the importance of registration, multiple sales, unofficial charges, and lack of transparency exacerbate the problem. This study examines the potential of blockchain technology to address these systemic issues. Blockchain's decentralized and secure framework offers transformative potential by enhancing transparency, reducing fraud, and streamlining land registration processes. Drawing from global applications, the paper highlights blockchain's ability to create tamper-proof records, minimize human errors, and build public trust in land transactions. However, significant challenges to adoption in Nigeria include technical and infrastructural limitations, regulatory challenges, political resistance, and the need to train stakeholders. The study proposes a strategic framework focused on private permissioned blockchains, smart contracts, and integration with existing land records to ensure gradual implementation. Adopting blockchain could significantly reduce registration timelines, lower costs, improve transparency, and foster economic growth through a reliable and secure land tenure system. This research highlights blockchain's potential to modernize land administration in Nigeria while addressing critical challenges and enabling equitable access to land rights.
Keywords: Blockchain; Land registration; Cadastre; Technology; Infrastructure